Results 1 to 3 of 3

Math Help - help with a few problems (don't need to answer all)

  1. #1
    Newbie
    Joined
    Sep 2008
    Posts
    21

    help with a few problems (don't need to answer all)

    i have tried these many times and still can't get them.

    1) f(x)= ((5x^3)-(5x^2)+9x-9) / (x-1) when x < 1
    f(x)= (6x^2)-1x+a when x>=1

    What value is a to make the function continuous at 1?

    I tried making them equal to each other and putting x=1 but that didn't work.

    2) (e^2x) - (7e^x) + 6 = 0

    It says there are 2 solutions but I keep getting -33.1255 and that's not even one of them.

    3) y=loga(x) with the subscript being a. It passes through (28,1).

    What is the value of a?

    I have no idea what to do on this one.

    4) log2(x) + log2(x+3) = k

    Solve for x in terms of k.

    Again, I have no idea what to do. I can solve it if k is an integer but thats about it.

    Any help is greatly appreciated.
    Follow Math Help Forum on Facebook and Google+

  2. #2
    MHF Contributor
    Joined
    Apr 2008
    Posts
    1,092
    1. Your approach would normally work, except that the function \frac{5x^3 - 5x^2 + 9x - 9}{x - 1} has a discontinuity at x = 1. But what is the limit of the function? Factor the numerator to yield \frac{(5x^2 + 9)(x-1)}{x-1}. Then cancel the factors of x-1 and you are left with 5x^2 + 9. At x = 1, this function is equal to 14, so the limit is 14, and that is the function value you want for the other part of your function.

    2. Substitute u = e^x, yielding u^2 - 7u + 6 = 0. Then solve for u by factoring and identifying the roots: (u - 6)(u - 1) = 0, so u = 1 or 6. Hence e^x = 1 or e^x = 6. From e^x = 1 you have the solution x = 0, and from e^x = 6 you have the solution x = ln 6.

    3. This is an easy one. The equation y = \log_a x can be rewritten as a^y = x. With (28, 1) on the graph, we have a^1 = 28, or a = 28.

    4. You can combine the two logarithms to yield \log_2 (x(x+3)) = k, which can be written 2^k = x(x + 3), or x^2 + 3x - 2^k = 0. Now apply the quadratic formula: x = \frac{-3 \pm \sqrt{9 + 4\cdot 2^k}}{2}. Recognizing that x must be a positive number in order to evaluate the logarithm, we have x = \frac{-3 + \sqrt{9 + 2^{k+2}}}{2}.
    Follow Math Help Forum on Facebook and Google+

  3. #3
    Newbie
    Joined
    Sep 2008
    Posts
    21
    ooooooo. Those explanations were great. Thanks a lot.
    Follow Math Help Forum on Facebook and Google+

Similar Math Help Forum Discussions

  1. Replies: 1
    Last Post: October 4th 2010, 05:46 PM
  2. Replies: 1
    Last Post: November 13th 2009, 11:14 AM
  3. Need help on how to answer these problems.
    Posted in the Algebra Forum
    Replies: 1
    Last Post: November 4th 2009, 01:09 PM
  4. elementary math problems need answer
    Posted in the Math Topics Forum
    Replies: 3
    Last Post: May 8th 2009, 03:58 AM

Search Tags


/mathhelpforum @mathhelpforum